2011
DOI: 10.3390/v3050541
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Localization and Cellular Factors Interaction of HTLV-1 and HTLV-2 Tax Proteins: Similarities and Functional Differences

Abstract: Human T-lymphotropic viruses type 1 (HTLV-1) and type 2 (HTLV-2) present very similar genomic structures but HTLV-1 is more pathogenic than HTLV-2. Is this difference due to their transactivating Tax proteins, Tax-1 and Tax-2, which are responsible for viral and cellular gene activation? Do Tax-1 and Tax-2 differ in their cellular localization and in their interaction pattern with cellular factors? In this review, we summarize Tax-1 and Tax-2 structural and phenotypic properties, their interaction with factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 113 publications
(149 reference statements)
1
45
0
Order By: Relevance
“…In the noncanonical pathway, Tax-1-IKK␥ interaction facilitates assembly of the Tax-1/IKK␣ complex, bypassing the requirement of NIK for IKK kinase activation (34)(35)(36)(37). Unlike Tax-1, Tax-2 is able to activate only the canonical NF-B route (38,39). Besides binding to IKK␥ in the cytoplasm, Tax-1 promotes NF-B activation in the nucleus by interacting with RelA and stabilizing the binding of p50/RelA to NF-B-responsive promoters (24,40).…”
mentioning
confidence: 99%
“…In the noncanonical pathway, Tax-1-IKK␥ interaction facilitates assembly of the Tax-1/IKK␣ complex, bypassing the requirement of NIK for IKK kinase activation (34)(35)(36)(37). Unlike Tax-1, Tax-2 is able to activate only the canonical NF-B route (38,39). Besides binding to IKK␥ in the cytoplasm, Tax-1 promotes NF-B activation in the nucleus by interacting with RelA and stabilizing the binding of p50/RelA to NF-B-responsive promoters (24,40).…”
mentioning
confidence: 99%
“…The differential functional characteristics of Tax1 and Tax2 most likely explain the differences in disease conditions associated with HTLV-1 and HTLV-2. 8 In clinical scenarios where overexpression of Tax1 and Tax2 occurs, increased transactivation of cellular genes might result in immune dysregulation in affected individuals. This has been clearly shown to be the case in HTLV-1-infected individuals with HTLV-1-associated myelopathy, in whom very high levels of HTLV-1 tax/rex mRNA can be detected.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Several recent studies suggest three conclusions regarding HIV/HTLV coinfections: (1) HIV-1 and HTLV-1 coinfections are often seen in the context of patients with high CD4 + T cell counts and who manifest neurological complications 5,6 ; (2) HIV-1 and HTLV-2 coinfections have been linked in some cases to a ''long-term nonprogressor'' phenotype 3,7 ; and (3) differential function and/or overexpression of the HTLV-1 and HTLV-2 Tax proteins are likely to play a pivotal role in the clinical and immunological manifestations of HIV/HTLV coinfections. 8 Two retrospective case-controlled cohort studies investigating the clinical outcomes and survival probabilities among persons coinfected with HIV-1 and HTLV-1 or -2 showed that HTLV-2 coinfections resulted in improved survival and delayed progression to AIDS. 3,7 These findings have been attributed in part to the ability of HTLV-2 to activate production of antiviral chemokines and to downregulate the CCR5 coreceptor on lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The kinases involved are unknown and could represent a genuine target for Tax-oriented therapy. Only the pleiotropic and constitutively active CK2 (formerly known as casein kinase 2) is proven to phosphorylate Tax in vitro, modulating the functions associated with its C-terminus [70] , which is extremely important for the binding, with subsequent inhibition, of class I PDZ-containing proteins, some of them tumor suppressors with scaffold function [98,99] . Furthermore, advanced and highly sensitive techniques, such as tandem mass spectrometry, struggle to detect Ser-300/301 phosphorylation or are entirely unable to detect Ser-160 phosphorylation, important for Tax function [69] .…”
Section: Tax Phosphorylationmentioning
confidence: 99%
“…A recent review described the known HTVL-1/2B Tax differences in NF-κB activation and localization, and showed how PTMs affect the two homologue proteins that share 85 % of sequence similarity [99] . HTLV-2B Tax is SUMOylated at lower levels than HTLV-1 Tax and ubiquitinated [100] .…”
Section: Tax-2b Ptmsmentioning
confidence: 99%